Eksistensi Perlindungan Hukum Secara Digitalisasi Bagi Wajib Pajak Selebgram Berdasarkan Administrasi Perpajakan Di Indonesia - Loupatty, Yopi; Nirahua, Salmon Eliazer Marthen; Tita, Heillen Martha Yosephine (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Selebgram as an income taxpayer has rights and obligations as a fundamental pillar.Purposes of the Research: This writing aims to discuss and analyze the digitalization of legal protection for taxpayers based on the provisions of tax administration in Indonesia.Methods of the Research: The type of research used is normative, which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field.Results of the Research: Legal protection, both prevention and repressive measures, has a good influence on all applications and websites for every celebgram taxpayer. The form of the site and application of new schemes in keeping up with current developments. The Call Center, Taxpayer Account, Cash Receipt System is half of the development of digitization used in Indonesia for legal protection for program taxpayers.